2002
DOI: 10.1007/s102650200007
|View full text |Cite
|
Sign up to set email alerts
|

Floral scent chemistry of mangrove plants

Abstract: The flowers of mangrove plants are pollinated by a variety of pollinators including birds, bats, and insects. This study analyzed the floral scent chemistry of mangroves on Iriomote Island (located near Taiwan) including Bruguiera gymnorrhiza (L.) Lamk. (Rhizophoraceae), Kandelia candel (L.) Druce (Rhizophoraceae), Rhizophora stylosa Griff. (Rhizophoraceae), Sonneratia alba J. Smith (Sonneratiaceae), Nypa fruticans (Thunb.) Wurmb. (Palmae), Lumnitzera racemosa Willd. (Combretaceae), Avicennia marina (Forsk.) V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 33 publications
2
24
0
4
Order By: Relevance
“…The characteristic wide distribution and long-range seed dispersal of mangrove plants may also favour a broad range of pollen vectors (Azuma et al, 2002). Mangroves are adapted to a generalized type of pollinators and thus competition for the available pollinators is reduced (Tomlinson, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic wide distribution and long-range seed dispersal of mangrove plants may also favour a broad range of pollen vectors (Azuma et al, 2002). Mangroves are adapted to a generalized type of pollinators and thus competition for the available pollinators is reduced (Tomlinson, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, less is known about floral biology, pollination, and breeding systems, although knowledge of the effectiveness of floral mechanics and genetic isolating mechanisms is an important prerequisite to the study of successful dispersal and establishment (Primack et al, 1981;Tomlinson, 1986;Juncosa and Tomlinson, 1987;Clarke and Meyerscough, 1991;Azuma et al, 2002;Ge et al, 2003;Chiou-Rong et al, 2005;Coupland et al, 2006). In India, a few studies provide some preliminary accounts of floral biology and pollination in some mangrove plants (Solomon Raju, 1990;Solomon Raju et al, 1994;Subba Reddi and Solomon Raju, 1997;Solomon Raju and Jonathan, 2008;Jonathan and Solomon Raju, 2009;Pandit and Choudhury, 2001;Jonathan, 2009;Rama Mohan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu potensi dari tumbuhan nipa yang belum dimanfaatkan adalah buah nipa. Sebagai tumbuhan berjenis palm, maka buah nipa memiliki kandungan karbohidrat, abu, air, energi, protein dan asam lemak [4].…”
Section: Pendahuluanunclassified
“…Conversely, the scent of myophilous and melittophilous palms was found to contain a mixture of numerous compounds in smaller total amounts, indicating that scent is probably less important than visual cues. Azuma et al (2002) included Nypa fruticans in a general study of floral scents emitted by mangrove plant species and revealed a high content of four different carotenoid derivaties that are known to attract insects. Among these were a beta-ionone which is highly attractive to certain beetles (Donaldson et al, 1990).…”
Section: Floral Scentmentioning
confidence: 99%